Photobleaching Reveals Heterogeneous Stoichiometry for Equinatoxin II Oligomers. Issue 14 (19th August 2014) - Baker, Matthew A. B.; Rojko, Nejc; Cronin, Bríd; Anderluh, Gregor; Wallace, Mark I.
Abstract Equinatoxin II (EqtII), a sea anemone cytolysin, is known to oligomerize to form pores that spontaneously insert into membranes. Crystallographic and cryo‐EM studies of structurally similar cytolysins offer contradictory evidence for pore stoichiometry. Here we used single‐molecule photobleaching of fluorescently labeled EqtII to determine the stoichiometry of EqtII oligomers in supported lipid bilayers. A frequency analysis of photobleaching steps revealed a log‐normal distribution of stoichiometries with a mean of 3.4±2.3 standard deviations. Comparison of our experimental data with simulations of fixed stoichiometries supports our observation of a heterogeneous distribution of EqtII oligomerization. These data are consistent with a model of EqtII stoichiometry where pores are on average tetrameric, but with large variation in the number of subunits in individual pores.